2021
DOI: 10.1088/1742-6596/1796/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

The concept of eco-friendly schools: The application of science education in shaping children’s characters to the environment

Abstract: This research was conducted to complement the existing learning by mapping carefully the child-friendly learning model applied at the Pelangi Alam School, Ponorogo, and how schools instill good habits through environmentally friendly exploration activities carried out in each lesson. This study used a qualitative phenomenological method by trying to understand the concept of environmental love by providing science and applying it to the environment. In addition, students also practiced science in understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The natural school creates an innovative and unique educational model, by offering a different learning experience that is difficult to achieve by other institutions/schools where learning is more interactive and practical involving the natural environment as a source of learning. Research has shown that spending time in nature can improve cognitive function, increase creativity, reduce stress, and improve physical health (Muafiah, Afifah, Nurohman, Huda, & Siswadi, 2021). Nature-based learning can also foster a sense of connectedness and responsibility to the environment, as well as helping students develop skills such as problem solving, teamwork and critical thinking (Burns & Manouchehri, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The natural school creates an innovative and unique educational model, by offering a different learning experience that is difficult to achieve by other institutions/schools where learning is more interactive and practical involving the natural environment as a source of learning. Research has shown that spending time in nature can improve cognitive function, increase creativity, reduce stress, and improve physical health (Muafiah, Afifah, Nurohman, Huda, & Siswadi, 2021). Nature-based learning can also foster a sense of connectedness and responsibility to the environment, as well as helping students develop skills such as problem solving, teamwork and critical thinking (Burns & Manouchehri, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Cultivating character that increases discipline, of course, requires conceptual steps that are referred to, given guidance and implemented in everyday life. (Muafiah, 2021). In achieving this form of discipline that can be directed at character education such as honesty, sportsmanship, politeness, empathy and good manners.…”
Section: Introductionmentioning
confidence: 99%